Phase change materials (PCMs) integrated into transparent building elements: A review - Fokaides, Paris A.; Kylili, Angeliki; Kalogirou, Soteris A. (My University, 2015)
Phase change materials (PCMs) represent an innovative solution that can contribute to the improvement of the energy performance of buildings. Recently a trend towards integrating PCMs into transparent envelope components is observed. This study aims to present the main solutions proposed in the literature for applications in the past few years for PCMs integrated into transparent buildings elements. The temporal development of this application as well as the fundamental principles of its operation is described in detail. The concept of the existing transparent PCM systems is presented, and the rationale of selecting appropriate materials is discussed. This is followed by the current practices in testing the thermal performance of transparent PCMs. The future trends in terms of the current barriers and the potential improvements are discussed. To this end the future technologies of transparent PCMs are also considered.
Keywords: Building elements; Phase change materials (PCMs); Transparent